Kritik des Antisemitismus in der Gegenwart Erscheinungsformen - Theorien - Bekämpfung - Grigat, Stephan (Interdisziplinäre Antisemitismusforschung/Interdisciplinary Studies on Antisemitism, 2023)
This volume is dedicated to the reconstruction of antisemitic consciousness and the depiction of the modifications of antisemitic resentment in order to sound out conditions and opportunities for a contemporary critique of antisemitism. Based on Adorno's categorical imperative, the volume combines theoretical analyses with practical considerations on how to combat antisemitism in all its current manifestations. A special focus is placed on Israel-related and Islamist antisemitism. The editor of the volume heads the Centre for Antisemitism and Racism Studies (CARS) in Aachen. With contributions by Markus Baum | Daniel Burghardt | Ingo Elbe | Alex Feuerherdt | Thorsten Fuchshuber | Marlene Gallner | Stephan Grigat | Matthias Küntzel | Florian Markl | Ulrike Marz | Elke Rajal | Samuel Salzborn | Gerhard Scheit